Amino acid chelated iron versus an iron salt in the treatment of iron deficiency anemia with pregnancy: A randomized controlled study. (March 2017) - Abdel Moety, Ghada Abdel Fattah; Ali, Ahmed Mahmoud; Fouad, Reham; Ramadan, Wafaa; Belal, Doaa Shafie; Haggag, Hisham Mamdouh
Abstract: Objective: The aim of this study was to compare the efficacy and tolerability of iron amino acid chelate (IAAC) and ferrous fumarate (FF) in treatment of iron deficiency anemia (IDA) with pregnancy. Study design: A total of 150 pregnant women having iron deficiency anemia (IDA) were randomized to receive either IAAC or FF for 12 weeks. Hemoglobin, red cell indices, serum iron, and serum ferritin were measured at baseline and then 4, 8, and 12 weeks after treatment. Adverse effects were questioned in both groups. Results: The mean values of hemoglobin, red cell indices, serum iron, and serum ferritin were not significantly different between both groups after 12 weeks of treatment. However, the rise in hemoglobin level after 4, 8, and 12 weeks of treatment was significantly faster in the IAAC group ( p = <0.001). Constipation and abdominal colicky pain were significantly more common in the FF group ( p = 0.022 and 0.031 respectively). Conclusion: IAAC and FF are comparable in curing IDA with pregnancy; however, IAAC has the advantage of providing a faster rate of improvement of hemoglobin level and is better tolerated by the patients.